Ocular toxicity from systemically administered xenobiotics - Gokulgandhi, Mitan R (Expert Opin Drug Metab Toxicol, 2012)
INTRODUCTION: The eye is considered as the most privileged organ because of the blood–ocular barrier that acts as a barrier to systemically administered xenobiotics. However, there has been a significant increase in the number of reports on systemic drug-induced ocular complications. If such complications are left untreated, then it may cause permanent damage to vision. Hence, knowledge of most recent updates on ever-increasing reports of such toxicities has become imperative to develop better therapy while minimizing toxicities. AREAS COVERED: The article is mainly divided into anterior and posterior segment manifestations caused by systemically administered drugs. The anterior segment is further elaborated on corneal complications where as the posterior segment is focused on optic nerve, retinal and vitreous complications. Furthermore, this article includes recent updates on acute and chronic ocular predicaments, in addition to discussing various associated symptoms caused by drugs. EXPERT OPINION: Direct correlation of ocular toxicities due to systemic drug therapy is evident from current literature. Therefore, it is necessary to have detailed documentation of these complications to improve understanding and predict toxicities. We made an attempt to ensure that the reader is aware of the characteristic ocular complications, the potential for irreversible drug toxicity and indications for cessation.